Pemberdayaan Wanita Petani Melalui Partisipasi dan Kapasitas di Kawasan Wisata Kambo - Muhammad Zainal Syafruddin; Adi Riyanto Suprayitno; Sapar Sapar; Marhani Marhani; Sri Mulia Dea; Andi Suprianto (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Introduction: Empowering female farmers in tourist areas is important to strengthen personal potential, collaboration skills, and sustainable agriculture. This study investigates the role of participation and capacity building in empowering women farmers in the Kambo tourist area. Objective: The study aims to examine how capacity building and involvement affect women farmers' empowerment. Variables studied include participation and capacity enhancement as free variables (X) and freedom as bound variables (Y). Methodology: "The research employed an explanatory design with 23 respondents, using Smart PLS for hypothesis testing." The research was conducted in the Kambo Tourism Area for four months, from April to June 2023. The research population is a member of the rural women actively following various programs, particularly the Village Building Advances Capacity Enhancement in the Fields of Agriculture, Health, and Tourism Based on Local Natural Potential Supporting Independence in the Village of Kambo". The research population was 23 female farmers actively participating in various programs, especially the Village Development Program through Capacity Building in the Fields of Agriculture, Health, and Tourism Based on Local Natural Potential Supporting Independence in Kambo Village. Sampling is done by taking a sample of the entire population using a census technique. Techniques for gathering data include organized interviews using questionnaires to gather information and data about the variable under study and observation by watching respondents. Results: "Participation significantly influenced empowerment, while capacity building showed no significant direct effect."